NUMERICAL EVALUATION OF WALL POROSITY ON HYDROMAGNETIC SLIP FLOW DUE TO VARIABLE THERMAL CONDUCTIVITY - Hamza, Muhammed Murtala; Sani, Dahiru; Ojemeri, Godwin (Journal of Engineering and Technology (JET), 2024)
In boundary layer control, especially in engineering, aerodynamics, space research, and medicine, suction/injection factors are very crucial. These advantages prompted our interest to dig further into the effect of wall porosity in industrial working fluids. Therefore, this paper analyses unsteady magnetized flow through an upstanding plate with the involvement of suction/injection flow and Navier slip flow due to the actions of variable buoyancy force and thermal conductivity distributions. The nonlinear partial differential equations for momentum and energy are modeled under the Boussinesq assumption using a semi implicit finite difference scheme, while the analytical results of the steady-state equations were calculated employing the regular perturbation technique. The solutions obtained were presented and discussed in detail using various line graphs. It is concluded that the slip flow parameter promotes fluid velocity, while the same effect occurs when the injection parameter is increased. However, a counter-feature can be observed: higher suction and magnetic parameters values lead to a drastic reduction in fluid movement respectively. The outcomes of this study would be helpful for controlling fluid flow in channels as well as aiding the addition and removal of reactants during chemical reactions.